Analisis Respons Dinamik Jembatan Rangka Baja Menggunakan Sistem Seismic Isolation Lead Rubber Bearing (LRB) - Ari Vera Indra; Reni Suryanita; Ismeddiyanto Ismeddiyanto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Seismic isolation is system to dampen seismic energy that works on the bridge by add an object called base isolators. The purpose of this study is show the dynamic response of steel truss bridge with stiffness variation LRB (Lead Rubber Bearing) as base isolators and seismic loads. Modeling the structure of the steel truss bridge consists of three spans and two poles. The steel truss bridge model given in the form of data akselerogram seismic load time history. The data is akselerogram Padang Earthquake Malaysia station with variations PGA (Peak Ground Acceleration) of 0.2 g, 0.4 g, 0.6 g and 0.8 g. LRB rigidity is increase to 50%, 100%, 150%, 200%, and 250% of the initial stiffness parameters LRB. The analysis is conduct use dynamic time history analysis. Stiffness value of LRB (Lead Rubber Bearing) base FEMA P-751-2012 and AASHTO Guide Specification for Seismic Isolation Design. Analysis showed The dynamic response displacement and decreased to increase stiffness of LRB but dynamic response acceleration increases.Keywords: Seismic isolation, base isolator, steel truss bridge,, PGA, Peak Ground Acceleration, LRB (Lead Rubber Bearing), dynamic time history analysis,, dynamic response.